2009
DOI: 10.1177/147323000903700120
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Microarray Assessment of Selenoprotein P Expression in Gastric Adenocarcinoma

Abstract: This study investigated selenoprotein P expression, using immunohistochemistry, in gastric adenocarcinoma tissue microarrays constructed from 30 gastric adenocarcinoma specimens and 30 normal gastric tissues (controls). Selenoprotein P expression scores were significantly lower in gastric adenocarcinoma (17/30, 56.7%) than in control tissues (25/30, 83.3%). Selenoprotein P was significantly more likely to be expressed in well-tomoderately differentiated cases (13/17, 76.5%) than in cases with low differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…[41][42][43][44][45][46][47] The quantitative analysis of serum SeP in this study using ELISA revealed a marked decrease in SeP levels in HCC group as compared to CLD and healthy control groups (p < 0.01). These results confirmed the findings of Li et al 48 who reported that SeP mRNA expression was significantly lower in HCC tissues compared to that of normal liver and cirrhosis, suggesting that SeP might play a role in the occurrence and development of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45][46][47] The quantitative analysis of serum SeP in this study using ELISA revealed a marked decrease in SeP levels in HCC group as compared to CLD and healthy control groups (p < 0.01). These results confirmed the findings of Li et al 48 who reported that SeP mRNA expression was significantly lower in HCC tissues compared to that of normal liver and cirrhosis, suggesting that SeP might play a role in the occurrence and development of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Core annular flow with the water-in-oil emulsion in the core surrounded by a water layer developed at high water fractions and mixture velocities. The formation of core annular flow in the experiments of Wang et al [25] can be linked to the self-lubricated bitumen froth reported in Joseph et al [20] and Sanders et al [24] In these studies, the formation of core annular flow requires high flow rates under which the water migrates into the wall region of high shear.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Also, the free water fraction of self-lubricated bitumen froth was less than 10 % of the total froth volume, which is much lower than the water fraction that would normally be considered feasible for stable waterlubricated transport of viscous crude oils. [24] Wang et al [25] experimentally investigated the concurrent flow of heavy crude and water in a horizontal steel pipe. The crude oil (viscosity around 628 mPa Á s at 60 8C) and water were collected from an oil field.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the increased SELENOP in M2 macrophages may offset the loss of SELENOP in tumor cells and support metastasis by supplying this in a paracrine manner, although this has not been tested experimentally. This may depend also on the location of cancer as a study of gastric adenocarcinoma found that SELENOP expression was low in cancer tissues compared with control tissues and was related to the degree of gastric adenocarcinoma differentiation but not to tumor node metastasis stage (Wang et al, 2009). …”
Section: Other Potential Roles For Selenoproteins In Metastasismentioning
confidence: 99%